Potensi Disalahgunakannya Aktivitas Penanaman Modal Asing sebagai Media Tindak Pidana Pencucian Uang di Indonesia - Kristian, Otniel Yustisia (Pusat Pelaporan dan Analisis Transaksi Keuangan (PPATK), 2024)
To attract significant foreign investment and boost national economic growth, it is essential to examine the risks of Foreign Direct Investment (FDI) misuse as a medium for Money Laundering (ML) in Indonesia. This study explores the potential misuse of FDI in facilitating ML, identifies the vulnerabilities, and recommends policy measures to address these risks. Using a normative legal research approach, the study found that FDI activities in Indonesia are vulnerable to misuse due to the lack of technical regulations mandating verification of shareholder authenticity and paid-up capital during company registration. Additionally, inadequate coordination between financial institutions, the Financial Transaction Reports and Analysis Center (INTRAC), and the Investment Coordinating Board (BKPM) exacerbates the issue. To mitigate ML risks in FDI, the study highlights the need to strengthen the anti-money laundering regime, enhance regulatory frameworks in the investment sector aligned with Financial Action Task Force (FATF) Recommendation 24 on transparency and beneficial ownership, and promote synergy among key stakeholders.